2018
DOI: 10.1002/ece3.4047
|View full text |Cite
|
Sign up to set email alerts
|

Immunological larval polyphenism in the map butterfly Araschnia levana reveals the photoperiodic modulation of immunity

Abstract: The bivoltine European map butterfly (Araschnia levana) displays seasonal polyphenism characterized by the formation of two remarkably distinct dorsal wing phenotypes: The spring generation (A. levana levana) is predominantly orange with black spots and develops from diapause pupae, whereas the summer generation (A. levana prorsa) has black, white, and orange bands and develops from subitaneous pupae. The choice between spring or summer imagoes is regulated by the photoperiod during larval and prepupal develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…This raises the question about how well can we extrapolate the laboratory‐based results to natural conditions. This aspect is also relevant for interpreting the studies on P. napi (Prasai & Karlsson, ) and A. levana (Baudach et al., ) that reported differences in the immunity between two different developmental pathways relying on laboratory measurements. One of the most significant results in the present study is the good correlation in measured traits between the laboratory and wild grown individuals.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This raises the question about how well can we extrapolate the laboratory‐based results to natural conditions. This aspect is also relevant for interpreting the studies on P. napi (Prasai & Karlsson, ) and A. levana (Baudach et al., ) that reported differences in the immunity between two different developmental pathways relying on laboratory measurements. One of the most significant results in the present study is the good correlation in measured traits between the laboratory and wild grown individuals.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study investigating the differences in induced immunity in different developmental pathways of A. levana is in good correlation with our predictions. It showed that also in the case of artificial immune challenge, the larvae entering the diapause had higher survival and higher induced antibacterial activity than directly developing ones (Baudach et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the genes among those differentially expressed in prepupae according to the day length during larval development encodes an A. levana ortholog of the silkworm ( Bombyx mori ) diapause bioclock protein which is known to be responsible for measuring the duration of diapause (Isobe et al, 2006). Moreover, a recent investigation has shown that photoperiodic modulation of phenotypes involve changes in life‐history traits of A. levana , featuring stronger innate immune responses upon challenge with the bacterial entomopathogen Pseudomonas entomophila in short‐day larvae (resulting in spring imagoes) in comparison to long‐day larvae (resulting in spring imagoes; Baudach, Lee, Vogel, & Vilcinskas, 2018).…”
Section: Introductionmentioning
confidence: 99%